Traumatic maxillofacial injuries: Patterns, outcomes, and long‐term follow‐up of a military cohort. Issue 2 (7th November 2022) - Tsur, Nir; Talmy, Tomer; Radomislensky, Irina; Almog, Ofer; Gendler, Sami
Abstract: Background/Aims: Maxillofacial trauma poses a distinct challenge on the modern battlefield, and data on its long‐term implications are scarce. The aim of this study was to investigate maxillofacial injury characteristics, outcomes, and complications along the continuum of care among hospitalized military personnel from the pre‐hospital setting through long‐term rehabilitation. Materials and Methods: A registry‐based study was undertaken of three national trauma and rehabilitation registries: The Israel Defense Forces Trauma Registry (IDF‐TR), which records pre‐hospital data. The Israeli National Trauma Registry for in‐hospital data and the Israel Ministry of Defense Rehabilitation Department (MOD‐RD) registry contain long‐term disability data. The cohort comprised IDF soldiers who suffered maxillofacial injuries between 1997 and 2020. Results: A total of 672 patients with maxillofacial injuries were included in the study, and 6.4% of all trauma admissions were related to maxillofacial injuries. Of these, 366 (54%) were injured in non‐military (NMC) circumstances, and 306 (46%) were wounded in military circumstances (MC). The mechanisms of injury were mainly traffic‐related among the NMC group compared with an explosion in the MC group. Maxillofacial fractures were frequently associated with traumatic brain injuries with higher rates in the NMC group than in the MC group (55% vs. 30%, p < .001). In a multivariate analysis, zygomatic and orbital fractures were associated with higher odds of concomitant head injury. The most common categories of long‐term disability included central nervous system disorders, skull injuries, epilepsy, hearing impairment, ophthalmologic conditions, and post‐traumatic stress disorder. Conclusions: Maxillofacial injuries are often associated with concomitant traumatic brain injury. Long‐term disabilities associated with these injuries included the central nervous system, hearing, ophthalmologic impairments, and post‐traumatic stress disorder.